Tcp Performance Optimization In Interaction With Mac Layer Over Multi-Hop Ad-Hoc Networks - Armaghani, Farzaneh R. (2008)

(untitled)
Transport Control Protocol (TCP) has been designed to provide reliable data delivery between end hosts in traditional wired networks and is the most widely used reliable transport protocol over the internet. TCP keeps looking at the traffic inside the network by employing the congestion control mechanisms. The basic assumption underlying TCP congestion control is that packet losses are an indication of congestion in the wired network. The effect of such an assumption on TCP's performance in wireless environments has been a long-standing research study. The reason is specific wireless properties such as high medium access contention; route breakage and high bit error rate in radio channels pose different challenges in TCP performance when it runs over wireless networks. In this thesis, the focus is given on the interaction between TCP and Medium Access Control (MAC) layer in multi-hop ad-hoc networks to deal with the effect of high medium access contention on TCP throughput. The main problem of TCP over IEEE 802.11 MAC protocol is the extensive number of medium access carried out by TCP. In fact, TCP sender will be informed of successful transmissions by receiving the acknowledgment (ACK) from the other end host to achieve the reliability. In this way, the MAC overhead may be caused by generating redundant ACK packets that compete in the same route with data packets for the media. As the load increases, the well-known hidden terminal effects caused by interference between ACK and data packets can degrade TCP performance dramatically if TCP acknowledges every incoming data packets. To address above problem, in this thesis a dynamic TCP-MAC interaction strategy is proposed which tries to reduce the number of induced ACKs by monitoring the channel condition. To this end, the total collision probability collected along the path from sender to receiver in MAC layer is used to properly set the number of the delayed ACKs (DA) in TCP. Based on the measured collision probability, TCP sender dynamically adjusts itself to the channel condition by delaying less ACKs in high traffics and more in low traffic conditions. Upon this strategy, an enhanced TCP throughput has been achieved in trade-off between moderate and high traffics. Finally, the relationship between the TCP throughput and optimized number of delayed ACKs has been investigated in different hop counts scenarios which employ a dynamic traffic. The findings show that for a given hop count, there exists an optimized delay window size which maximizes the TCP throughput. Overall, the achieved throughput increments are up to about 30% over the regular TCP with DA extension and cwnd limit and about 10% over the existing method called Dynamic Adaptive Acknowledgment (TCP-DAA and TCP-DAAp).